The Impact of Biologic Therapy Introduction on Hip and Knee Replacement Among Rheumatoid Arthritis Patients: An Interrupted Time Series Analysis Using the Clinical Practice Research Datalink - Hawley, S; Cordtz, R; Dreyer, L; Edwards, C; Arden, N; Delmestri, A; Cooper, C; Judge, A; Prieto-Alhambra, D (American College of Rheumatology, 2016)
In several developed countries it has been observed that the incidence of orthopaedic surgery among rheumatoid arthritis (RA) patients has been in decline, despite a concurrent increase among non-RA patients. Whilst the introduction of biologic therapies may be an explanatory factor for the divergent trends, specific data testing this hypothesis is lacking. We set out to estimate the impact of approval and national guidance (National Institute for Health and Care Excellence (NICE) TA36) on anti-tumour necrosis factor alpha (TNF-α) therapy use for RA on rates of total hip (THR) and knee replacement (TKR) among incident RA patients.